LC50 of arsenic in Tehuelche scallop Aequipecten tehuelchus from San José Gulf in Patagonia, Argentina - Sturla Lompre, Julieta (2017)
The fishing industry is an important economic activity in Argentina, and in recent years there was a trend of growth in exports, being the main consumer countries Spain (27%) and China (14%) (Ministry of Agro Industry, 2016). In 2015, 11% of total exportation of marine resources were mollusks (Ministry of Agro Industry, 2016). Among the main commercial species of bivalves are the mussel Mytilus edulis platensis, the Tehuelche scallop Aequipecten tehuelchus, the Patagonian scallop Zygochlamys patagonica and the ribbed mussel Aulacomya atra. Seafood is considered as the main source of arsenic (As) in the human diet (Mania et al., 2015; Muñoz et al., 2005; Sigrist et al., 2016) and recent reports have shown the presence of this metalloid in some mollusks (Mohamed, 2008; Urtubey et al., 2016) and also in seaweed from North Patagonian Gulfs (Gil et al., 2015). San Jose Gulf is located in northern Patagonia (42º20´S, 64º20´W) in Valdes Peninsula and presents geographical and ecological conditions favorable for the settlement of natural populations of great commercial interest. In this place, scallop has historically represented the support species of the shellfish activity especially for the families of artisanal fishermen who live there. Thus, the human influence on the ecosystem is scarce and limited to artisanal shellfish activity and is not contaminated by urban-industrial effluents (Neyro, 2017).The goal of the present study was to determine environmental concentrations of As in seawater, sediment, and tissues of scallops, and to defined its LC50 by bioassays performed in independent aquariums.